Preparation method of membrane material for solar cell backboard
By applying a functional coating of specific ratios on the back panel of solar cell and using modified silica and a variety of functional additives, the shortcomings of existing resin films in terms of weather resistance, interlayer binding force and water resistance are solved, and the performance and service life of the back panel are significantly improved.
Patent Information
- Application Number
- CN202411857365.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
The existing resin film for solar cell backplane is insufficient in terms of weather resistance, interlayer bonding force, water barrier performance, etc., and cannot meet the service life requirements of solar cell modules for more than 25 years.
Using a specific coating structure, a high-performance resin film is formed through the introduction of modified silica, combined with a variety of functional additives such as solubilizers, plasticizers, anti-UV agents and dispersants. Modified silica is prepared by a dual modification process of co-grafting and free radical copolymerization of organosilane compounds, which significantly improves the weather resistance and protective properties of the film.
It significantly improves the weather resistance, protection performance and service life of the solar cell backplane, ensures stable performance during long-term outdoor use, and meets the multiple performance requirements of solar cell modules.
Smart Images

Figure BDA0005192217180000091 
Figure BDA0005192217180000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar cells, and in particular to the technical field of solar cell backplane film materials. Background Art
[0002] In the manufacturing process of solar cell modules, the backsheet, as the outermost protective material, plays a vital role in ensuring the long-term reliability and service life of solar cell modules. The backsheet needs to have excellent weather resistance, insulation, water resistance and mechanical strength, as well as good interlayer adhesion to protect the internal solar cells from erosion and damage by environmental factors. As a commonly used backsheet material, resin film is widely used due to its cost advantage and basic performance.
[0003] Most of the existing resin films for solar cell backplanes have problems such as insufficient weather resistance, poor interlayer bonding, and poor water barrier properties. In particular, many existing resin films are prone to yellowing, cracking, and peeling under long-term outdoor exposure conditions, and cannot meet the service life requirements of solar cell modules of more than 25 years. In addition, the resin films in the prior art often perform poorly in terms of UV resistance, water barrier properties, and interlayer adhesion, and cannot simultaneously meet the multiple performance requirements of solar cell backplanes. Therefore, the development of a resin film with excellent weather resistance, good water barrier properties, and high interlayer bonding has become a technical problem that the solar cell module manufacturing industry urgently needs to solve.
[0004] The resin film of the present invention has multiple advantages. First, it adopts a coating structure with a specific formula, and provides excellent water resistance and weather resistance through the introduction of modified silica. Through the carefully designed resin formula and additive system, it has excellent interlayer adhesion and mechanical strength, ensuring stable performance during long-term outdoor use. At the same time, the preparation process of the resin film is simple and controllable, which is conducive to large-scale production and reduces manufacturing costs. In addition, the materials used are environmentally friendly and safe, meet the sustainable development requirements of the modern photovoltaic industry, and significantly improve the performance and service life of the solar cell backplane as a whole. Summary of the invention
[0005] The present invention can solve the technical problem that the prior art battery backplane film has insufficient performance in terms of UV resistance, water barrier performance and interlayer adhesion, and cannot simultaneously meet the multiple performance requirements of the solar cell backplane. In order to solve at least one of the above problems, the present invention provides a film material for a solar cell backplane, including a resin base film and a first coating, wherein the first coating is composed of the following raw materials in parts by weight:
[0006] Resin 20-30 parts;
[0007] 10-20 parts of modified silicon dioxide;
[0008] 10-20 parts of solubilizer;
[0009] 5-15 parts of plasticizer;
[0010] 10-15 parts of anti-ultraviolet agent;
[0011] Dispersant 10-15 parts;
[0012] The present invention provides a method for preparing a film material for a solar cell back panel, the method comprising the following steps:
[0013] S100: preparing a first coating stock solution for use in the first coating;
[0014] S200: applying the first coating stock solution onto the resin base film;
[0015] S300: Drying to obtain a solar cell back panel film.
[0016] In the above technical solution, S100 specifically includes:
[0017] S101: adding anhydrous ethanol or butyl acetate to a constant temperature mixer, and continuing to add the resin to obtain a first mixed solution, wherein the resin is an acrylic resin or an epoxy resin;
[0018] S102: adding the modified silicon dioxide to the first mixed solution, and continuing to add the solubilizer, the plasticizer, and the anti-ultraviolet agent to obtain the first coating stock solution.
[0019] In the above technical solution, the solubilizing agent is dimethyl sulfoxide or N-methylpyrrolidone;
[0020] In the above technical solution, the plasticizer is epoxidized soybean oil or citrate;
[0021] In the above technical solution, the anti-ultraviolet agent is a diphenyltriazine type ultraviolet agent;
[0022] In the above technical solution, the dispersant is a polycarboxylic acid dispersant;
[0023] In the above technical scheme, the preparation method of modified silica is: co-grafting nano-silica with an organic silane compound to obtain co-modified silica, and then performing free radical copolymerization on the surface of the co-modified silica to obtain;
[0024] The organosilane compound is tridecafluorooctyltrimethoxysilane and / or hexadecyltrimethoxysilane, and vinyltrimethoxysilane;
[0025] The preparation steps of modified silica include:
[0026] S401: Under nitrogen protection, dispersing 10-20 parts of nano-silicon dioxide in a mixed solution of anhydrous ethanol and deionized water to obtain a second mixed solution, wherein the mass ratio of anhydrous ethanol to deionized water is 4:1;
[0027] S402: adjusting the pH value of the second mixed solution to 4-5 by dropwise adding dilute acetic acid, sequentially adding 5-10 parts of hexadecyltrimethoxysilane and / or tridecafluorooctyltrimethoxysilane and 5-10 parts of vinyltrimethoxysilane, and reacting at 70-75° C. for 4-6 hours to obtain a co-modified silica stock solution;
[0028] S403: separating the solid product in the co-modified silica stock solution by centrifugation, and drying the solid product in a vacuum drying oven to obtain the co-modified silica;
[0029] S404: under nitrogen protection, dispersing 10-20 parts of the co-modified silica in anhydrous ethanol, adding 5-10 parts of methacryloyloxyethyl trimethyl ammonium chloride, heating to 60-70° C., dropping 0.2-0.5 parts of ammonium persulfate solution, reacting at 60-70° C. for 6-8 hours to obtain a modified silica stock solution;
[0030] S405: Separate the solid product in the modified silicon dioxide stock solution by centrifugation, and dry it in a vacuum drying oven at 60° C. to obtain the modified silicon dioxide.
[0031] Step S300 specifically includes:
[0032] S301: using a casting coating method or a roller coating method, coating the first coating stock solution on the surface of the film substrate;
[0033] S302: pre-drying at 80°C for 10 minutes;
[0034] S303: Curing at 150°C for 30 minutes.
[0035] This application can significantly improve the weather resistance and protective performance of the solar cell backplane by coating a functional coating with a specific component ratio on a resin-based film and using modified silicon dioxide as a key additive, ensuring that the solar cell has good stability and reliability during long-term outdoor use. Compared with the traditional resin film preparation method, this application innovatively adopts a dual modification process of co-grafting of organic silane compounds and free radical copolymerization to prepare modified silicon dioxide. By precisely controlling the coating formula components and preparation process parameters, it solves the problems of easy aging, poor weather resistance, and insufficient protective performance of solar cell backplanes in the prior art. This method not only has a reasonable and controllable process flow, but also effectively overcomes the technical defects of poor coating adhesion, insufficient weather resistance, and short service life that are prone to occur in traditional battery backplane films in actual applications through the synergistic effect of functional additives such as solubilizers, plasticizers, and anti-ultraviolet agents. DETAILED DESCRIPTION
[0036] The purpose of the present invention is to provide a high-performance solar cell backplane resin film with excellent weather resistance, protective performance and service life, and can adapt to the harsh environment of long-term outdoor use of solar cells. The resin film comprises a resin base film and a functional coating structure, and the selection of coating components and the preparation process are precisely optimized to achieve excellent protective effects. The present invention aims to provide a solar cell backplane material with excellent performance and reliable application through an innovative modified silica preparation process combined with the synergistic effect of multiple functional additives.
[0037] To achieve the above purpose, the method adopted by the present invention is to apply a functional coating of a specific ratio on a resin-based film, and by precisely controlling the raw material components and process parameters, each component can give full play to its performance advantages. The coating formula includes resin (20-30 parts), modified silica (10-20 parts), solubilizer (10-20 parts), plasticizer (5-15 parts), anti-ultraviolet agent (10-15 parts) and dispersant (10-15 parts), wherein the modified silica is prepared by a double modification process of co-grafting of organic silane compounds and free radical copolymerization to ensure that it has excellent dispersibility and functionality; the coating preparation process adopts a cast coating or roller coating process, and through a pre-drying and high-temperature curing process, this method not only improves the bonding force between the coating and the substrate, but also significantly enhances the weather resistance and protective performance of the product, ensuring that the battery backplane film exhibits excellent performance and long-term stability in the actual application of solar cells.
[0038] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.
[0039] The experimental methods in the following examples without specifying specific conditions were carried out according to conventional methods and conditions, or selected according to the product instructions.
[0040] The raw materials used in the following Examples 1 to 3 and Comparative Examples 1 to 3 are as follows:
[0041] Membrane: Toray F32, 75 μm thickness.
[0042] Acrylic resin: Rohm and Haas B-44.
[0043] Epoxy resin: Dow Chemical DER671.
[0044] Nano-silicon dioxide: Degussa AEROSIL 200.
[0045] Cetyltrimethoxysilane: Shin-Etsu Chemical KBM-3063.
[0046] Tridecafluorooctyltrimethoxysilane: Geiel FluoroSyl 3750.
[0047] Vinyltrimethoxysilane: Dow Corning Z-6518.
[0048] Methacryloyloxyethyltrimethylammonium chloride: Sigma-Aldrich 440159.
[0049] Dimethyl sulfoxide (DMSO): Sigma-Aldrich D8418.
[0050] N-Methylpyrrolidone (NMP): BASF N-Methylpyrrolidone.
[0051] Epoxidized soybean oil: ADEKA ARGUS EP-8 from Aekyung Chemical.
[0052] Citrate esters: Vertellus CITROFLEX A-4.
[0053] Diphenyltriazine UV agent: BASF Tinuvin 400.
[0054] Polycarboxylic acid dispersant: BYK-2155.
[0055] Example 1
[0056] A method for preparing a solar cell backplane resin film, the raw material parts used below are by mass, and the specific steps are as follows:
[0057] S1: dispersing 15 parts of nano-silicon dioxide in a mixed solution of anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 4:1) to obtain a second mixed solution;
[0058] S2: The pH value was adjusted to 4.5 by dropping 1 mol / L dilute acetic acid, and 8 parts of hexadecyltrimethoxysilane and 7 parts of vinyltrimethoxysilane were added in sequence, and the mixture was reacted at 72°C for 5 hours to obtain a co-modified silica stock solution;
[0059] S3: Separate the solid product using a centrifuge (8000 r / min, 20 min), and dry it in a vacuum drying oven at 60° C. for 12 h to obtain co-modified silica;
[0060] S4: Under nitrogen protection, 15 parts of co-modified silica were dispersed in anhydrous ethanol, 8 parts of methacryloyloxyethyl trimethyl ammonium chloride were added, the mixture was heated to 65° C., 0.3 parts of ammonium persulfate solution was added dropwise, and the mixture was reacted at 65° C. for 7 hours to obtain a modified silica stock solution;
[0061] S5: Separate the solid product using a centrifuge (8000 r / min, 20 min), and dry it in a vacuum drying oven at 60° C. for 12 h to obtain the final modified silica;
[0062] S6: Add 500 mL of anhydrous ethanol to the constant temperature mixer, and continue to add 25 parts of acrylic resin, stirring at a speed of 500 r / min and a temperature of 30° C., and stir for 2 hours until completely dissolved to obtain a first mixed solution;
[0063] S7: Add the following into the first mixed solution in sequence: 15 parts of modified silica, 15 parts of dimethyl sulfoxide (DMSO) as a solubilizer, 10 parts of epoxy soybean oil as a plasticizer, 12 parts of diphenyl triazine UV agent as an anti-ultraviolet agent, and 12 parts of polycarboxylic acid dispersant as a dispersant; increase the stirring speed to 800 r / min, maintain the temperature at 30°C, and continue stirring for 3 hours to obtain a first coating stock solution;
[0064] S8: using a casting coater, coating the first coating solution on the film surface with a wet film thickness of 20 μm; S9: pre-drying at 80° C. for 10 minutes;
[0065] S10: Curing at 150°C for 30 minutes.
[0066] Example 2
[0067] Some of the raw materials in Example 1 are replaced as follows:
[0068] The resin was changed to 28 parts of epoxy resin;
[0069] The solubilizer was changed to 18 parts of N-methylpyrrolidone;
[0070] The plasticizer is changed to 12 parts of citrate;
[0071] The remaining steps are the same as those in Example 1.
[0072] Example 3
[0073] Some of the raw materials in Example 1 are replaced as follows:
[0074] The organosilane compound was replaced by 9 parts of tridecafluorooctyltrimethoxysilane;
[0075] The amount of dispersant was adjusted to 14 parts;
[0076] The amount of anti-ultraviolet agent is adjusted to 14 parts;
[0077] The remaining steps are the same as those in Example 1.
[0078] Comparative Example 1
[0079] A method for preparing a solar cell backplane resin film, the specific steps are as follows:
[0080] Preparation of silica dispersion
[0081] S1: dispersing 15 parts of nano-silicon dioxide in a mixed solution of anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 4:1) to obtain a silicon dioxide dispersion;
[0082] S2: Use a centrifuge (8000 r / min, 20 min) to separate the solid product, and dry it in a vacuum drying oven at 60° C. for 12 hours to obtain treated silicon dioxide.
[0083] Preparation of the first coating solution
[0084] S3: Add 500 mL of anhydrous ethanol to a constant temperature mixer, and continue to add 25 parts of acrylic resin, stirring at a speed of 500 r / min and a temperature of 30° C., and stir for 2 hours until completely dissolved to obtain a first mixed solution;
[0085] S4: Add the following into the first mixed solution:
[0086] 15 parts of treated silicon dioxide;
[0087] Solubilizer: 15 parts of dimethyl sulfoxide;
[0088] Plasticizer: 10 parts of epoxidized soybean oil;
[0089] Anti-ultraviolet agent: 12 parts of diphenyltriazine ultraviolet agent;
[0090] Dispersant: 12 parts of polycarboxylic acid dispersant;
[0091] The stirring speed was increased to 800 r / min, the temperature was maintained at 30°C, and stirring was continued for 3 hours to obtain the first coating stock solution;
[0092] S5: using a casting coater, coating the first coating solution on the film surface with a wet film thickness of 20 μm; S6: pre-drying at 80° C. for 10 minutes;
[0093] S7: Curing at 150°C for 30 minutes.
[0094] Comparative Example 2
[0095] A method for preparing a solar cell backplane resin film, the specific steps are as follows:
[0096] S1: Under nitrogen protection, 15 parts of nano-silicon dioxide are dispersed in a mixed solution of anhydrous ethanol and deionized water (the mass ratio of anhydrous ethanol to deionized water is 4:1) to obtain a second mixed solution;
[0097] S2: The pH value was adjusted to 4.5 by dropping 1 mol / L dilute acetic acid, 8 parts of hexadecyltrimethoxysilane were added, and the mixture was reacted at 72°C for 5 hours to obtain a modified silica stock solution;
[0098] S3: The solid product was separated using a centrifuge (8000 r / min, 20 min), and dried in a vacuum drying oven at 60° C. for 12 h to obtain a single modified silica;
[0099] S4: Add 500 mL of anhydrous ethanol to the constant temperature mixer, and continue to add 25 parts of acrylic resin, stirring at a speed of 500 r / min and a temperature of 30° C., and stir for 2 hours until completely dissolved to obtain a first mixed solution;
[0100] S5: Add the following into the first mixed solution:
[0101] 15 parts of single modified silica;
[0102] Solubilizer: 15 parts of dimethyl sulfoxide;
[0103] Plasticizer: 10 parts of epoxidized soybean oil;
[0104] Anti-ultraviolet agent: 12 parts of diphenyltriazine ultraviolet agent;
[0105] Dispersant: 12 parts of polycarboxylic acid dispersant;
[0106] The stirring speed was increased to 800 r / min, the temperature was maintained at 30°C, and stirring was continued for 3 hours to obtain the first coating stock solution;
[0107] S6: Use a casting coater to apply the first coating solution to the film surface with a wet film thickness of 20 μm; S7: Pre-dry at 80° C. for 10 minutes;
[0108] S8: Curing at 150°C for 30 minutes.
[0109] Comparative Example 3
[0110] S1: dispersing 15 parts of nano-silicon dioxide in a mixed solution of anhydrous ethanol and deionized water (mass ratio 4:1) to obtain a silicon dioxide dispersion;
[0111] S2: Separate the solid product using a centrifuge (8000 r / min, 20 min), and dry it in a vacuum drying oven at 60° C. for 12 hours to obtain treated silicon dioxide;
[0112] S4: Add 500 mL of anhydrous ethanol to the constant temperature mixer, and continue to add 25 parts of acrylic resin, stirring at a speed of 500 r / min and a temperature of 30° C., and stir for 2 hours until completely dissolved to obtain a first mixed solution;
[0113] S5: Add the following into the first mixed solution:
[0114] 15 parts of unmodified silicon dioxide;
[0115] Plasticizer: dibutyl phthalate (DBP) 10 parts;
[0116] Anti-ultraviolet agent: 12 parts of benzotriazole ultraviolet absorber;
[0117] Dispersant: 12 parts of polycarboxylic acid dispersant;
[0118] The stirring speed was increased to 800 r / min, the temperature was maintained at 30°C, and stirring was continued for 3 hours to obtain the first coating stock solution;
[0119] S6: Using a casting coater, the first coating solution was coated on the surface of the film (thickness 75 μm) with a wet film thickness of 20 μm;
[0120] S7: pre-drying at 80°C for 10 minutes;
[0121] S8: Curing at 150°C for 30 minutes.
[0122] Performance Testing
[0123] The performance test results of the samples obtained in Examples 1 to 3 and Comparative Examples 1 to 3 are listed in Table 1 Adhesion Test
[0124] Test standard: GB / T 9286-1998;
[0125] Test method: cross-cut method;
[0126] Rating criteria:
[0127] Level 0: The edges of the cross-section are completely smooth and without any shedding;
[0128] Level 1: There is slight peeling at the grid intersection, and the peeling area does not exceed 5%;
[0129] Level 2: There is peeling along the cut edge and / or grid intersection, and the peeling area is 5%-15%;
[0130] Level 3: peeling area 15%-35%;
[0131] Level 4: peeling area 35%-65%;
[0132] Level 5: The peeling area is greater than 65%.
[0133] Wear resistance test
[0134] Test standard: GB / T 1768-2006;
[0135] Test index: weight loss percentage.
[0136] Water vapor transmission rate test
[0137] Test standard: GB / T 26873-2011;
[0138] Test conditions: Temperature: 38±0.5℃;
[0139] Relative humidity: 90±2%;
[0140] Table 1
[0141]
[0142]
[0143] Comparative Example 1 shows that the unmodified silica has poor dispersibility and poor compatibility with the substrate, resulting in a significant decrease in coating performance;
[0144] Comparative Example 2 shows that a single modification process cannot achieve good dispersibility and functionality at the same time, and the performance improvement effect is limited;
[0145] Comparative Example 3 adopts the traditional formula, and its performance indicators are inferior to those of the solution of the present invention, especially in terms of wear resistance and adhesion.
[0146] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a film material for a solar cell back sheet, characterized in that: The film material of the battery back sheet includes a resin base film and a first coating layer, wherein the first coating layer is composed of the following raw materials in parts by weight: Resin 20-30 parts; 10-20 parts of modified silicon dioxide; 10-20 parts of solubilizer; 5-15 parts of plasticizer; 10-15 parts of anti-ultraviolet agent; Dispersant 10-15 parts; The preparation method comprises: S100: preparing a first coating stock solution for use in the first coating; S200: applying the first coating stock solution onto the resin base film; S300: Drying to obtain a solar cell back panel film.
2. The method for preparing a film material for a solar cell back sheet according to claim 1, characterized in that: The step S100 specifically includes: S101: adding anhydrous ethanol or butyl acetate to a constant temperature mixer, and continuing to add the resin to obtain a first mixed solution, wherein the resin is an acrylic resin or an epoxy resin; S102: adding the modified silicon dioxide to the first mixed solution, and continuing to add the solubilizer, the plasticizer, and the anti-ultraviolet agent to obtain the first coating stock solution.
3. The method for preparing a film material for a solar cell back sheet according to claim 2, characterized in that: The solubilizing agent is dimethyl sulfoxide or N-methylpyrrolidone.
4. The method for preparing a film material for a solar cell back sheet according to claim 2, characterized in that: The plasticizer is epoxidized soybean oil or citrate.
5. The method for preparing a film material for a solar cell back sheet according to claim 2, characterized in that: The anti-ultraviolet agent is a diphenyltriazine type ultraviolet agent.
6. The method for preparing a film material for a solar cell back sheet according to claim 2, characterized in that: The dispersant is a polycarboxylic acid dispersant.
7. A method for preparing a film material for a solar cell back sheet according to any one of claims 1 to 6, characterized in that: The preparation method of the modified silicon dioxide is as follows: co-grafting nano silicon dioxide with an organic silane compound to obtain co-modified silicon dioxide, and then copolymerizing the co-modified silicon dioxide on the surface of the co-modified silicon dioxide through free radical copolymerization.
8. The method for preparing a film material for a solar cell back sheet according to claim 7, characterized in that: The organic silane compound is tridecafluorooctyltrimethoxysilane and / or hexadecyltrimethoxysilane, and vinyltrimethoxysilane.
9. The method for preparing a film material for a solar cell back sheet according to claim 7, characterized in that: The preparation steps of the modified silicon dioxide include: The parts of raw materials used in the following preparation processes are all parts by mass; S401: dispersing 10-20 parts of nano-silicon dioxide in a mixed solution of anhydrous ethanol and deionized water to obtain a second mixed solution, wherein the mass ratio of anhydrous ethanol to deionized water is 4:1; S402: adjusting the pH value of the second mixed solution to 4-5 by dropwise adding dilute acetic acid, sequentially adding 5-10 parts of hexadecyltrimethoxysilane and / or tridecafluorooctyltrimethoxysilane and 5-10 parts of vinyltrimethoxysilane, and reacting at 70-75° C. for 4-6 hours to obtain a co-modified silica stock solution; S403: separating the solid product in the co-modified silica stock solution by centrifugation, and drying the solid product in a vacuum drying oven to obtain the co-modified silica; S404: under nitrogen protection, dispersing 10-20 parts of the co-modified silica in anhydrous ethanol, adding 5-10 parts of methacryloyloxyethyl trimethyl ammonium chloride, heating to 60-70° C., dropping 0.2-0.5 parts of ammonium persulfate solution, reacting at 60-70° C. for 6-8 hours to obtain a modified silica stock solution; S405: Separate the solid product in the modified silicon dioxide stock solution by centrifugation, and dry it in a vacuum drying oven at 60° C. to obtain the modified silicon dioxide.
10. A method for preparing a film material for a solar cell back sheet according to any one of claims 1 to 6, characterized in that: The step S300 specifically includes: S301: using a casting coating method or a roller coating method, coating the first coating stock solution on the surface of the film substrate; S302: pre-drying at 80°C for 10 minutes; S303: Curing at 150°C for 30 minutes.